Sustainable Professional Development: Skills and Needs for Scientific Publication Training for Elementary School Teachers - Wahyudin, Undang Ruslan; BK, Muhamad Taufik (Jurnal Pendidikan Indonesia, 2022)
Scientific publications are one of the components for teachers to develop their profession in a sustainable manner. Written works published by teachers are part of the characteristics of professional teachers through the culture of writing and researching. On the other hand, scientific publications are also an effort to improve the mastery of science and skills in carrying out lifelong learning for teachers. This study aims to gather information, analyze, and describe the ability, training needs of elementary school teachers in scientific publications including the inhibiting factors and the solutions needed. The study was conducted using a mixed research method with an explanatory design involving 87 elementary school teachers. Data was collected through survey techniques, interviews, documentation, and observation. Data analysis was carried out using quantitative, qualitative and triangulation descriptive techniques. The results of the study indicate that although socialization and training on continuous professional development are received by teachers, the fact is that the knowledge and skills of teachers in scientific publications are still very low. Some of the inhibiting factors for teachers in scientific publications include lack of mastery of scientific writing techniques, lack of IT skills, Weak scientific writing skills, low teacher literacy, lack of available references, motivation, time, widespread scientific writing services, and lack of training. Alternative solutions that can be recommended include 1) improvement of the higher education system, especially Educational Personnel Education Institutions, and 2) education and training based on the needs of teachers in scientific publications.